2020
DOI: 10.1021/acs.jafc.0c00874
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Release and Nontoxic Pickering Emulsion Platform for Antimicrobial Peptide

Abstract: The resistance in microorganisms against many conventional antibiotics has become a serious global health problem. However, antibacterial drug delivery materials are still limited in toxicity, short efficacy and reducing inflammation. The novel and natural Pickering emulsions stabilized by antimicrobial peptide nanoparticles were tested as promising platforms to control bacterial resistance development. The parasin I interacted or conjugated with lecithin or chitosan and formed nanoparticles encapsulated by Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…In fact, this crystallinity modification could be attributed to PVP, which may have surrounded the crystal aggregates of phlorotannin during the preparation of PPNPS, thus forming an amorphous shell [ 25 ]. These results are consistent with previous reports which showed that the physical state of lutein was converted from crystalline to amorphous due to encapsulation and the chemical interactions between lutein and PVP during nanoparticle preparation [ 20 ]. These characterization results combined with the embedding rate of phlorotannin show that the ratio of 1:8 would be appropriate for making PPNPS based on its good particle size and effective embedding rate.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, this crystallinity modification could be attributed to PVP, which may have surrounded the crystal aggregates of phlorotannin during the preparation of PPNPS, thus forming an amorphous shell [ 25 ]. These results are consistent with previous reports which showed that the physical state of lutein was converted from crystalline to amorphous due to encapsulation and the chemical interactions between lutein and PVP during nanoparticle preparation [ 20 ]. These characterization results combined with the embedding rate of phlorotannin show that the ratio of 1:8 would be appropriate for making PPNPS based on its good particle size and effective embedding rate.…”
Section: Resultssupporting
confidence: 93%
“…This suggested that encapsulation of PVP caused an expansion of the nanoparticles, which is a common phenomenon reported in the literature [ 19 ]. The FTIR measurement was performed to verify the encapsulation of phlorotannin inside the PVP shell [ 20 ]. As shown in Figure 1 c, when the FTIR spectra of the PPNPS, phlorotannin and phlorotannin + PVP mixture were compared, it was clear that some of the peaks associated with specific functional groups in the phlorotannin molecules (e.g., 1546 cm −1 ) only appeared in the spectrum of the mixture, but not in that of the PPNPS.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of functional food prepared with PMEs for application in medicine seems to be very promising. It is worth mentioning that Cai et al, 2020 reported the potential application of Pickering emulsions with antibacterial and anti-inflammatory effects [ 155 ].…”
Section: Potential Application Of Pmes In Food Systemsmentioning
confidence: 99%
“…Pickering emulsions can also be developed into sustained-release nontoxic platforms for antimicrobial peptides. For example, Cai et al [ 342 ] controlled the emergence of bacterial drug resistance using a stable Pickering emulsion with antimicrobial peptide nanoparticles (formed by the interaction of the catfish antimicrobial peptide with lecithin or chitosan), and they achieved milder and more effective anti-inflammatory effects in the case of peritonitis. Such systems may therefore provide a means to combat the issues related to multidrug-resistant bacteria in biomedical applications.…”
Section: Applications On the Macrostructure Scalementioning
confidence: 99%